Chakana and Thirdspace: Engaging Ecuadorian STS in Places of Knowledge Co-Production - María Belén Albornoz (Engaging Science, Technology, and Society, 2023)
Ecuadorian STS studies connects to earlier Latin American scholars’ concerns over science and technology. Like many other academic communities, Ecuadorian STS emerged from the collision of scholarly interest, the building of new research centers, and opportunities for collaboration among undergraduate and postgraduate programs. Primarily rooted in the need to develop social technologies these studies form part of a regional movement aimed at questioning: technological dependence, the role of science in peripheral contexts, and public policies of science, technology, and innovation. The ways in which an STS academic community forms around Ecuadorian STS—is in this case, less about a network than—a matter concerning Henri LeFebvre’s “trialectics of spatiality” ([1974] 1991). In particular, Homi Bhabba (1994) and Edward Soja’s (1996) contributions to the decolonial development of a “thirdspace” is understood as a “particular way of thinking about and interpreting socially produced space” (ibid.). This essay offers a reflection on identity (re-)formation in the making of community. Developing a thirdspace as a transformative process draws inspiration from the Chakana, an Andean symbol of wisdom. A specifically decolonial thirdspace unfolds through the three ascending–descending steps of the Chakana that represent both the expansion and the sustaining of the community: 1. as an Andean referencing point (evoking the bridging-staircase symbol); 2. which allows for the co-creation of situated knowledge from different transnational STS genealogies located in Latin America; 3. and as an obligatory point of passage for STS community creation through identity building. Conceptualizing Ecuadorian STS as a thirdspace, helps to socially comprehend community formation as a social process that is also a critique of symbolic space for membership and knowledge production. By discussing why place is fundamental in community institutionalization, this essay creates possibilities to comprehend—dimensions of STS in the Global South—socially, politically, and cognitively.